Legal Protection Of Consumer Data Of E-Commerce - Hermawanto, Dedi; Amiq, Bachrul; Subekti, Subekti (Ipso Jure, 2024)
This research will explore the use of technology so that it can strengthen the legal system in Indonesia and examine best legal practices in various countries to improve consumer data protection in e-commerce. Consumer protection legal research is increasingly urgent given the risks that continue to evolve and have a significant impact on consumers. The formulation of this research problem is: 1) How is the protection of business civil law in providing protection for consumers related to the misuse of consumer personal data in e-commerce transactions? 2) What are the legal actions against the misuse of consumer data in e-commerce? This thesis research uses normative legal types on consumer protection and misuse of personal data while also researching legal aspects that regulate consumer rights and the protection of unauthorized users. The results of the study show that the protection of consumers' personal data in e-commerce transactions in Indonesia is regulated by various laws and regulations, which are relevant to the civil law aspects of business. Cases of misuse of consumer data in e-commerce have encouraged increased awareness of the importance of protecting consumer rights in civil relations between consumers and business actors.